Production and characterization of hydrogel with chia seed oil-loaded nanocapsules - Martins, Elenice Spagnolo Rodrigues; Felin, Sabrina; Viana, Altevir Rossato; Silva, Solange Cristina da; Krause, Luciana Maria Fontanari; Souza, Diego de; Boeck, Carina Rodrigues (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
The present work aims to develop and characterize a hydrophilic gel containing nanocapsules within chia oil for topical application of natural products as a promising alternative to prevent and treat wound. The chia oil-nanocapsules (NCCO) suspension was developmented and a hydrogel formulation was produced. The gel was tested for characterization and stability for 90. Toxicity tests were carried out for NCCO, chia oil in natura and free chia oil-nanocapsules in murine B16F10 skin melanoma cells. The NCCO showed a particle diameter of 246.23 ± 1.53 nm and a polydispersity index of 0.148 ± 0.08. The nanocapsules within hydrogel formulation displayed pH 4.80 ± 0.07, inicial viscosity 14960 ± 426.66 9 cP and spreadability 4599.05 ± 1304.27 mm². The hydrogel under low temperature (± 4ºC) maitained stability for 90 days without changes on odor, color and visual aspect. The NCCO suspension was not able to induce cytotoxicity in tumoral lineage cells. After all, the conclusion is that the hydrogel containing NCCO showed feasibility to be applied dermatologically on skin care.